Accelerating an integrative view of quantum biology - Kinsey, Luke J.; Beane, Wendy S.; Tseng, Kelly Ai-Sun (Frontiers in Physiology, 2024)
Quantum biology studies span multiple disciplines including physics, engineering, and biology with the goal of understanding the quantum underpinnings of living systems. Recent findings have brought wide attention to the role of quantum mechanisms in the function and regulation of biological processes. Moreover, a number of activities have been integral in building a vibrant quantum biology community. Due to the inherent interdisciplinary nature of the field, it is a challenge for quantum biology researchers to integrate and advance findings across the physical and biological disciplines. Here we outline achievable approaches to developing a shared platformincluding the establishment of standardized manipulation tools and sensors, and a common scientific lexicon. Building a shared community framework is also crucial for fostering robust interdisciplinary collaborations, enhancing knowledge sharing, and diversifying participation in quantum biology. A unified approach promises not only to deepen our understanding of biological systems at a quantum level but also to accelerate the frontiers of medical and technological innovations.